Defining Recovery in Schizophrenia: A Review of Outcome Studies - Berrios-Espinoza, R (Elsevier Ireland Ltd, 2023)
Schizophrenia is a chronic disorder with a heterogenous course and different ways in which recovery is measured or perceived. Recovery in schizophrenia is a complex process that it can be defined either from a clinical perspective focused on sustained symptom and functional remission, or from a patient-focused one, as a self-broadening process aimed at living a meaningful life beyond mental illness. Until now, studies analysed these domains separately, without examining their mutual relations and changes over time. Therefore, this meta-analysis aimed to examine the relationship of global measures of subjective recovery with each of the components of clinical recovery such as symptom severity and functioning, in patients with schizophrenia spectrum disorders. The results showed that the association between different indicators of personal recovery and remission are weak and inverse (dIG+ = –0.18, z = –2.71, p < 0.01), however, this finding is not substantial according to the sensitivity indicators. With respect to functionality and personal recovery, there was a moderate relationship (dIG+ = 0.26, z = 7.894, p < 0.01) with adequate sensitivity indices. In addition, a low consensus exists between subjective measures that are more related to the patient s perspective and clinical measures based on experts and clinician s viewpoint. © 2023